Genetic Variants in EMT-Related lncRNAs Modulate the Risk of Colorectal Cancer in the Chinese Population - Simeng Gu; Zhaohui Zhang; Keyi Cheng; Aibuta Yeerken; Sangni Qian; Fanjia Guo; Mingjuan Jin; Kun Chen (Biochemical Genetics, 2026)

Novel quantitative method of reactive losses of ambient VOCs coupling chemical transport model simulation with receptor measurement - Yao Gu; Baoshuang Liu; Simeng Ma; Zhongwei Luo; Jinqiu Zhang; Danni Liang; Yafei Li; Yufen Zhang; Yinchang Feng (Journal of Hazardous Materials, 2025)

Osthole–pyrethrins combination loaded onto hollow microsphere silica nanoparticles inhibits Fusarium solani growth and controls root rot incidence in Cynanchum auriculatum - Xiaomeng Fei; Bing Xie; Junjie Tang; Lixia Wang; Yong Zheng; Haifeng Kuai; Simeng Li; Daoguo Zhang; Wei Gu (Physiological and Molecular Plant Pathology, 2025)

Thyroglobulin as a Sensitive Biomarker of Iodine Status in Mildly and Moderately Iodine-Deficient Pregnant Women - Yujie Jiang; Simeng Gu; Zhe Mo; Xueqing Li; Chenyang Liu; Yahui Li; Guangming Mao; Yuanyang Wang; Fanjia Guo; Xiaoming Lou; Xiaofeng Wang (Biological Trace Element Research, 2024)
Pregnant women are more susceptible to iodine deficiency. However, there are limitations in existing indicators for the evaluation of iodine nutrition in pregnant women. The study aimed to explore whether thyroglobulin (Tg) can be used as a more sensitive biomarker for pregnant women with mild and moderate iodine deficiency. A repeated-measure study was conducted among 1332 pregnant women in Zhejiang Province, China. Serum and urine specimens were collected at a mean of 10, 17, and 32 weeks of pregnancy, respectively; thyroid-stimulating hormone (TSH), Tg, and urinary iodine concentrations were measured. Linear mixed effects models were used to determine the associations between interaction of iodine concentrations and increasing gestation week and TSH and Tg, where participants were divided by urinary iodine concentration (UIC). The median Tg concentration was 11.56, 11.45, and 12.43 μg/L in the first, second, and third trimesters, respectively. After controlling the covariates, the interaction effects between the iodine status and gestation week were significant for both TSH and Tg ( p = 0.038 and p = 0.007, respectively). TSH increased with the week of gestation in both iodine concentration groups. Tg increased with advancing pregnancy in the iodine-deficient group whereas it did not in the iodine-sufficient group. There was no significant variation in TSH at each trimester, and Tg was higher in the iodine-deficient group than in the iodine-sufficient group. Tg may be a more sensitive iodine status biomarker than TSH for pregnant women with mild-to-moderate iodine insufficiency.

A tumor-responsive nanostrategy for reducing the risk of immunotherapy-related myocarditis - Mengjun Sui; Simeng Wang; Ye Zhou; Hui Dang; Zekun Zeng; Kunrong Gu; Hongxin Cao; Meiju Ji; Penggao Dai; Yangyang Cheng; Peng Hou (Chemical Engineering Journal, 2024)

The abundance and pathogenicity of microbes in automobile air conditioning filters across the typical cities of China and Europe - Kaifei Su; Zhishu Liang; Simeng Zhang; Wen Liao; Jianwei Gu; Yunlong Guo; Guiying Li; Taicheng An (Journal of Hazardous Materials, 2024)

Effect of light intensity on the accumulation of protostane triterpenes in Asian water plantain (Alisma orientale) - Wenqing Wu; Simeng Li; Wei Gu; Rong Tian; Man Luo; Junjie Tang; Min Tang; Yinzhi Wu (Acta Physiologiae Plantarum, 2024)

The effects of temperature variability on mortality in patients with chronic obstructive pulmonary disease: a time-series analysis in Hangzhou, China - Simeng Gu; Xiaofeng Wang; Guangming Mao; Xuemin Huang; Yuanyang Wang; Peiwei Xu; Lizhi Wu; Xiaoming Lou; Zhijian Chen; Zhe Mo (Environmental Science and Pollution Research, 2022)

Metabolomics changes in brain-gut axis after unpredictable chronic mild stress - Qiuyue Xu; Mingchen Jiang; Simeng Gu; Xunle Zhang; Guangkui Feng; Xianjun Ma; Shijun Xu; Erxi Wu; Jason H Huang; Fushun Wang (Psychopharmacology, 2022)
Background Major depressive disorder is a leading cause of disability worldwide, affecting up to 17 % of the general population. The neural mechanisms of depression, however, are yet to be uncovered. Recently, attention has been drawn to the effects of dysfunctional brain-gut axis on depression, and many substances have been suggested to be involved in the communication between the gut and brain, such as ghrelin. Methods We herein systematically examined the changes of metabolomics after unpredictable chronic mild stress (UCMS)–induced depression-like behaviors in rats and compared the altered metabolites in the hippocampus and jejunum samples. Results Our results show that many metabolites significantly changed with UCMS both in the hippocampus and jejunum, such as L-glutamine, L-tyrosine, hydroxylamine, and 3-phosphoglyceric acid. Further studies suggested that these changes are the reasons for anxiety-like behaviors and depression-like behaviors in UCMS rats and also are the reasons for hippocampal neural plasticity. Conclusions Coexistence of brain and gut metabolic changes in UCMS-induced depressive behavior in rats suggests a possible role of brain-gut axis in depression. This study provides insights into the neurobiology of depression.

NKCC1 up-regulation contributes to early post-traumatic seizures and increased post-traumatic seizure susceptibility - Fushun Wang; Xiaowei Wang; Lee A. Shapiro; Maria L. Cotrina; Weimin Liu; Ernest W. Wang; Simeng Gu; Wei Wang; Xiaosheng He; Maiken Nedergaard; Jason H. Huang (Brain Structure and Function, 2017)